1997
DOI: 10.1038/sj.onc.1201014
|View full text |Cite
|
Sign up to set email alerts
|

The retinoblastoma gene family is differentially expressed during embryogenesis

Abstract: We report di erential expression of the RB1 tumor suppressor gene and the homologous genes p107 and p130 during embryogenesis. Abundant RB1 transcripts were detected during neurogenesis, hematopoiesis, myogenesis, lens development and in the ganglion cell layer of the embryonic retina, prior to and during di erentiation. The expression pattern of RB1 mirrored the defects in RB1 mutant mice (RB 7/7 ). In the heart, lung, kidney and intestine, p107, but not RB1, was expressed. In the liver and the central nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 27 publications
11
97
0
2
Order By: Relevance
“…Recent data have also demonstrated that the di erent pRB-family proteins participate in the regulation of distinct E2F-responsive genes (Hurford et al, 1997). Taken together with their developmentally regulated patterns of expression (Dagnino et al, 1997a,b;Jiang et al, 1997), these experiments predict that the distinct members of the pRB-and E2F-families may not necessarily be redundant and have, in fact, tissue-speci®c roles and/or cell cycle-speci®c activities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent data have also demonstrated that the di erent pRB-family proteins participate in the regulation of distinct E2F-responsive genes (Hurford et al, 1997). Taken together with their developmentally regulated patterns of expression (Dagnino et al, 1997a,b;Jiang et al, 1997), these experiments predict that the distinct members of the pRB-and E2F-families may not necessarily be redundant and have, in fact, tissue-speci®c roles and/or cell cycle-speci®c activities.…”
Section: Discussionmentioning
confidence: 94%
“…However, E2F-4 and E2F-5 expression in the same system failed to overcome the block unless they were co-expressed with DP1. Together with the apparent restricted tissue speci®city of expression of some of the E2Fs (Dagnino et al, 1997a,b) and pRB-family proteins (Jiang et al, 1997), these data imply a complex cell cycle regulatory pathway where the speci®c outcomes may vary in di erent tissues and at di erent points during development.…”
Section: Introductionmentioning
confidence: 95%
“…Rb7/7 mutant embryos die at mid-gestation and develop speci®c abnormalities in neurogenesis, erythropoiesis and lens development. The spectrum of defects in Rb7/7 mutant embryos is consistent with the speci®c expression of Rb during embryogenesis in the nervous system, lens, liver and skeletal muscles (Jiang et al, 1997). Analysis of the role of Rb in older embryos was made possible by the use of a mouse Rb minigene, mgRb, which is expressed exclusively in the nervous system and can rescue the neurogenic defects of Rb7/7 embryos (Zacksenhaus et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Mice Pancreas-specific Rb knockout mice, Pdx1-Cre:Rb fl/fl (p-RbKO) [18], were bred to p107 −/− whole-body knockout mice (p107KO) (E. Zacksenhaus, Toronto, ON, Canada) [19] to generate Pdx1-Cre:Rb fl/fl /p107 −/− mice (p-DKO) and control Pdx1-Cre:Rb +/+ /p107 +/+ littermates. Mice were maintained on a mixed C57BL6;129/Sv background and housed as previously described [18].…”
Section: Methodsmentioning
confidence: 99%